Potential mechanism of circRNA_000585 in cholangiocarcinoma. Issue 6 (June 2021) - Yi, Fengming; Xin, Longxiang; Feng, Long
Objective: Circular RNA (circRNA) plays a vital role in the development and progression of malignancies, however, the function of circRNAs in cholangiocarcinoma (CCA) remains unexplored. The aim of this study was to investigate circRNA expression in CCA versus para-cancer tissues, and elucidate any potential associated mechanisms. Methods: Differential expression of circRNAs between CCA and para-cancer tissue was analysed by microarray hybridization, and validated by real-time quantitative reverse transcription–polymerase chain reaction (qRT–PCR). The downstream pathway was investigated using bioinformatics and qRT–PCR. Results: Microarray hybridization revealed 10 circRNAs with > 3-fold increased expression versus para-cancer (circRNA_002172, circRNA_002144, circRNA_001588, circRNA_000166, circRNA_000585, circRNA_000167, circRNA_402608, circRNA_006853, circRNA_001589, circRNA_008882), and three circRNAs with > 3-fold decreased expression (circRNA_406083, circRNA_104940, circRNA_006349). CircRNA_000585 was shown by qRT-PCR to be upregulated in tumour versus paired para-cancer tissue from 15 patients with CCA. Bioinformatics analysis revealed a potential pathway comprising circRNA_000585/microRNA-615-5p/angiomotin (AMOT)/Yes associated protein 1 (YAP) in CCA. RT–PCR validation of crucial molecule expression showed downregulation of miR-615-5p, and upregulation of AMOT and YAP in CCA tumours. Conclusion: Multiple circRNAs are dysregulated in CCA. CircRNA_000585 is upregulated in CCA, and may function by a circRNA_000585/miR-615-5p/AMOT/YAP pathway, which may be a novel CCA pathway.